THE DILEMMA OF ENFORCEMENT OF JUSTICE REHABILITATION FOR DRUG ABUSERS: A STUDY OF PRACTICES AND REGULATIONS - Agus Darmawan, M. Dandi; Josias Simon Runturambi, Arthur; Iskandar, Anang (NOMOI Law Review, 2025)
Law enforcement against drug abusers in Indonesia has tended to be oriented towards a repressive and punitive approach. This approach prioritizes imprisonment as the primary solution, without clearly distinguishing between pure criminals and drug abuse victims who actually need rehabilitation. As a result, correctional institutions are filled with drug users with high recidivism rates, while the goals of social recovery and public health are often neglected. This research is a normative juridical study with a statute approach. The results of the discussion indicate that although the rehabilitation justice approach aims to rehabilitate users and restore social relationships, its implementation is often hampered by a legal paradigm that still prioritizes the deterrent effect, limited understanding among law enforcement officials, a lack of rehabilitation facilities, public stigma, and weak coordination between relevant agencies. To strengthen the implementation of rehabilitation justice for drug abusers in Indonesia, it is necessary to improve understanding and training for law enforcement officials, strengthen coordination between relevant agencies, and expand rehabilitation facilities equitably, including the development of community-based programs.